A Verticillium dahliae Pectate Lyase Induces Plant Immune Responses and Contributes to Virulence - Yang, Yuankun; Zhang, Yi; Li, Beibei; Yang, Xiufen; Dong, Yijie; Qiu, Dewen (Frontiers in Plant Science, 2018)
Verticillium dahliae is a wide-host-range fungal pathogen that causes soil-borne diseases in hundreds of dicotyledonous hosts. In search of V. dahliae Vd991 cell death-inducing proteins, we identified a pectate lyase (VdPEL1) that exhibited pectin hydrolytic activity, which could induce strong cell death in several plants. Purified VdPEL1 triggered defense responses and conferred resistance to Botrytis cinerea and V. dahliae in tobacco and cotton plants. Our results demonstrated that the mutant VdPEL1rec lacking the enzymatic activity lacked functions to induce both cell death and plant resistance, implying that the enzymatic activity was necessary. In addition, VdPEL1 was strongly induced in V. dahliae infected N. benthamiana and cotton roots, and VdPEL1 deletion strains severely compromised the virulence of V. dahliae. Our data suggested that VdPEL1 contributed to V. dahliae virulence and induced plant defense responses. These findings provide a new insight for the function of pectate lyase in the host-pathogen interaction.